Idiopathic histaminergic angioedema without wheals: a case series of 31 patients. (13th April 2016) - Faisant, C; Boccon-Gibod, I; Mansard, C; Dumestre Perard, C; Pralong, P; Chatain, C; Deroux, A; Bouillet, L
Summary: Idiopathic histaminergic acquired angioedema (IH-AAE) is a common cause of recurrent angioedema without wheals. It is a mast cell-mediated disease thought to belong to the same clinical entity as chronic urticaria (CU). The objective of this study was to describe the clinical and epidemiological characteristics of IH-AAE patients. From 2014 to 2015, 534 patients were seen at our national reference centre for angioedema and/or urticaria. Among them, we identified 31 patients with idiopathic histaminergic acquired angioedema without wheals (IH-AAE). Thirty-one patients (15 men and 16 women) with a mean age of 50 years met the criteria for IH-AAE. The average delay in diagnosis was 6·3 years. A history of allergy was found in 12 patients (38·7%), nine suffering from allergic rhinitis. The mean duration of attacks was 28·1 h. The AE attack was located in the upper respiratory tract in 54·8% of cases (17 patients). A lingual location was found in 29% of patients. Men were more likely than women to have an upper airway involvement. No intubations or admissions to intensive care units were reported. The dosage of anti-histamines to control the symptoms was onefold the recommended dose in 51·6% of patients (16 patients), twofold in 32% (10 patients) and three–fourfold in 16·1% (five patients). IH-AAE is characterized by an important delay in diagnosis, a frequent involvement of the upper airway and a benign course during attacks. As in CU, a trial of up to fourfold dose of H1-anti-histamines may be necessary to control symptoms.